2009
DOI: 10.1097/icb.0b013e31818c5de0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Central Retinal Artery Occlusion in a Patient With Acute Pancreatitis

Abstract: It is postulated that the resultant complement activation with subsequent leukoembolization along with the combined effect of other variables led to microvascular damage resulting in bilateral central retinal artery occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…In contrast, Xiao et al found more patients with abnormalities on carotid ultrasound, 89% as against 32% with abnormalities on echocardiography [19]. Acute pancreatitis which was seen in one patient in this study has been associated with bilateral RAO [20]. It is postulated that arterial occlusion occurs as a result of complement activation with subsequent leukoembolization [20].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In contrast, Xiao et al found more patients with abnormalities on carotid ultrasound, 89% as against 32% with abnormalities on echocardiography [19]. Acute pancreatitis which was seen in one patient in this study has been associated with bilateral RAO [20]. It is postulated that arterial occlusion occurs as a result of complement activation with subsequent leukoembolization [20].…”
Section: Discussioncontrasting
confidence: 65%
“…Acute pancreatitis which was seen in one patient in this study has been associated with bilateral RAO [20]. It is postulated that arterial occlusion occurs as a result of complement activation with subsequent leukoembolization [20]. Aggressive management of modi able risk factors is essential in preventing a repeat arterial occlusion in the fellow eye following a unilateral RAO as well as other life threatening vascular events.…”
Section: Discussionmentioning
confidence: 59%
“…There are a number of ways in which the retinal arteries can become blocked; the most common is by an embolus. Alternatively, there may be a sudden narrowing of the vessels due to atherosclerotic changes, vasculitis, vascular spasm, circulatory collapse, dissecting aneurysm, and hypertensive arterial necrosis [ 1 ]. Early recognition and treatment may preserve eye function.…”
Section: Introductionmentioning
confidence: 99%
“…WG is a rare, chronic multisystemic disease, with an annual incidence of ten cases per million population [ 4 , 5 ]. More common in Caucasians with a peak incidence in the fifth decade of life [ 6 ], WG has a predilection for affecting the upper and lower respiratory tracts and kidneys [ 1 , 7 ] and the eyes; central nervous system can also be affected [ 8 ].…”
Section: Introductionmentioning
confidence: 99%